2021
DOI: 10.1093/nar/gkab030
|View full text |Cite
|
Sign up to set email alerts
|

PAUPARand PAX6 sequentially regulate human embryonic stem cell cortical differentiation

Abstract: Long noncoding RNAs (lncRNAs) play a wide range of roles in the epigenetic regulation of crucial biological processes, but the functions of lncRNAs in cortical development are poorly understood. Using human embryonic stem cell (hESC)-based 2D neural differentiation approach and 3D cerebral organoid system, we identified that the lncRNA PAUPAR, which is adjacent to PAX6, plays essential roles in cortical differentiation by interacting with PAX6 to regulate the expression of a large number of neural genes. Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Overexpression of SOX1 could rescue the neuronal differentiation impairment caused by SOX1‐OT V1 inhibition. Our previous study showed that SOX1 could be regulated by PAX6 through PAX6 directly binding to the SOX1 gene region (Xu et al , 2021). In this study, we found that inhibition of SOX1‐OT V1 did not affect the expression of PAX6 but reduced the expression level of SOX1, suggesting that SOX1‐OT V1 functions as a novel regulator of SOX1 in a PAX6‐independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of SOX1 could rescue the neuronal differentiation impairment caused by SOX1‐OT V1 inhibition. Our previous study showed that SOX1 could be regulated by PAX6 through PAX6 directly binding to the SOX1 gene region (Xu et al , 2021). In this study, we found that inhibition of SOX1‐OT V1 did not affect the expression of PAX6 but reduced the expression level of SOX1, suggesting that SOX1‐OT V1 functions as a novel regulator of SOX1 in a PAX6‐independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Pnky can enhance neuronal differentiation (Ramos et al , 2015). LncRNA PAUPAR can interact with its adjacent transcription factor PAX6 and regulate hESC cortical differentiation (Xu et al , 2021). These studies suggested that lncRNAs play key regulatory roles in neural differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the human-specific LncRNA, SMILR , was investigated in organ cultures of human saphenous vein grafts to define its role in mediating smooth muscle cell proliferation (Mahmoud et al 2019 ). Meanwhile, the PAUPAR LncRNA was studied in human organoids and shown to regulate cortical differentiation (Xu et al 2021 ). These ex vivo model systems represent a higher order level of investigation over simple, two-dimensional cell culture models.…”
Section: Challenges Limitations and Alternative Approaches To Humanized Bac Micementioning
confidence: 99%
“…A relevant lncRNA with a cis -acting mechanism is Paupar ( Pax6 upstream antisense RNA), which is transcribed upstream the Pax6 gene in the opposite direction [ 104 ]. Paupar acts in cis regulating PAX6-dependent functions since its knockdown leads to an increase in PAX6 expression and interferes with eye development, progenitor cell potency and proliferation in the brain [ 104 , 105 ]. The exact molecular mechanism of regulation on the Pax6 is not entirely known, although it could be speculated that its transcription affects the nearby promoter region of Pax6 , either stabilizing transcription factor binding or inducing promoter-enhancer looping.…”
Section: Functional Classification Of Neuronal Lncrnasmentioning
confidence: 99%
“…In parallel, Paupar has probably evolved a more elaborate mechanism of action. In addition to regulating the expression of Pax6 , it also regulates the binding of PAX6 to its neural target genes [ 105 ] and acts in trans by forming a ribonucleoprotein (RNP) complex together with PAX6 and KAP1 (coded by Trim28 ), which is involved in transcriptional control [ 104 , 106 ]. It seems that Paupar promotes the association of KAP1 with the DNA resulting in H3K9me3 modifications on the promoter of genes involved in neural stem cell renewal and differentiation, inducing heterochromatin and inactivation [ 106 ].…”
Section: Functional Classification Of Neuronal Lncrnasmentioning
confidence: 99%